House at Lincoln
In districts where timber was plentiful, the medieval carpenter displayed his skills in house construction with the framed and braced type of structure seen here. The walls of each successive story are built on an extension of the floor beams to relieve pressure on the floor below. This system of construction was common through much of England, the space between the timbers being available in the locality- principles which are now in common use in contemporary framed buildings.